CHEMOSELECTIVE CATALYTIC HYDROGENATION OF ALKENES BY LINDLAR CATALYST - Ghosh, Arun K. (Tetrahedron Lett, 1999)
Commercially available Lindlar catalyst (10% by weight) in methanol, selectively hydrogenates various alkenes in the presence of benzyl ether and benzyl amine functionalities.